2018
DOI: 10.1371/journal.pone.0194240
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of medication selling and self-medication practices: A study from Punjab, Pakistan

Abstract: BackgroundAccess to medicines without prescription is a major contributing factor for self-medication practices. This study was designed to examine the ratio of non-prescribed medicines sales and self-medication practices in Punjab, Pakistan. This study also evaluates the reasons for self-medication within its communities.MethodsAn observational study was conducted in 272 systemically selected pharmacies to analyze medicines-related sales, with or without prescription. A cross-sectional survey was performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 36 publications
3
76
0
4
Order By: Relevance
“…On average, every pharmacy sold 7.9 drugs without prescription every day To an average of 5.5 customers. Many of them (28.9%) were metric in their education [11].…”
Section: Discussionmentioning
confidence: 99%
“…On average, every pharmacy sold 7.9 drugs without prescription every day To an average of 5.5 customers. Many of them (28.9%) were metric in their education [11].…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication is the selection and use of drugs and drug products by any person to treat selfrecognized or self-diagnosed conditions without proper diagnosis by physicians (1)(2)(3)(4)(5)(6)(7). it is a common practice of the health care system (7).…”
Section: Introductionmentioning
confidence: 99%
“…Self-medication drugs and drug products are called 'nonprescription' or 'over the counter' (OTC) which are available in the pharmacy without a prescription ordered by physicians or any other licensed prescribers (8). This includes purchasing medicine without a prescription, sharing medicine with relatives or members of the family (7,9). Currently more drugs and drug products has been changed from prescription-only medications to over the counter (pharmacy sell without prescription) medications (2) Self-medication can have bene ts and hazards and the the reasonable use of self-medication can save limited medical resources from being wasted on minor conditions, reduce the load of health facilities and decrease costs as well as the time spent to visit health care facilities for minor disease conditions (10).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 26/31 (84%) recruited study participants reported that they were given antibiotics as children (Table S1). Moreover, 'self-prescription' is another common issue in Pakistan [31], where individuals consume antibiotics on their own and sometimes insist doctors to prescribe them drugs.…”
Section: Introductionmentioning
confidence: 99%